ANALISA EFISIENSI PENGGUNAAN MODAL KERJA PADA USAHA KECIL “MIRA” DI KOTA PALEMBANG - Andini Utari Putri; Puspa Djuita (Sekolah Tinggi Ilmu Ekonomi (STIE) Aprin, 2019)
The Purpose of this study was to determine how much efficient the use of working capital by using ratio analysis in the culinary business “Mira” located in the city of Palembang by using financial statement data in the form of a balance sheet and income statement.To find out how much the level of efficiency in the use of working capital in the culinary business Mira.The author uses the analysis of liquidity ratio, activity ratio and profitability ratio. With the liquidity ratio, Mira’s ability to pay off obligations that must be fulfilled immediately is quite good. Because the ratio is above 200%. Although there was a decline in 2016 and 2017 but not too big. The company’s economic profitability ratio is quite efficient in using working capital,seen from the result of the economic profitability ratio in 2015 of 38% but in 2016 there was a decrease of 35.43% and in 2017 it will increase again to 42,3%. The shows that the company in using its working capital is quite efficientand from profitability ratio is also quite good because it is able to generate substantial profits.